Genome-wide identification of long intergenic non-coding RNAs for Ralstonia solanacearum resistance in tomato (Solanum lycopersicum) - Cao, Peina; Zhan, Chuang; Yin, Junliang; Gong, Shuangjun; Ma, Dongfang; Li, Yan (Frontiers in Plant Science, 2022)
There is growing evidences indicating that long intergenic ncRNAs (lincRNAs) play key roles in plant development and stress responses. To research tomato lincRNA functions during the interaction between tomato and Ralstonia solanacearum, RNA-seq data of tomato plants inoculated with R. solanacearum was analyzed. In this study, 315 possible lincRNAs were identified from RNA-seq data. Then 23 differentially expressed lincRNAs between tomato plants inoculated with R. solanacearum and control were identified and a total of 171 possible target genes for these differentially expressed lincRNAs were predicted. Through GO and KEGG analysis, we found that lincRNA might be involved in jasmonic acid and ethylene signaling pathways to respond to tomato bacterial wilt infection. Furthermore, lincRNA may also be involved in regulating the expression of AGO protein. Subsequently, analysis of expression patterns between differentially expressed lincRNAs and adjacent mRNAs by qRT-PCR revealed that part of lincRNAs and their possible target genes exhibited positive correlation. Taken together, these results suggest that lincRNAs play potential roles in tomato against R. solanacearum infection and will provide fundamental information about the lincRNA-based plant defense mechanisms.